Unilateral live twin tubal ectopic pregnancy presenting at 12 weeks of gestation: A case report. Issue 38 (September 2019) - Seak, Chen-June; Goh, Zhong Ning Leonard; Wong, Alexis Ching; Seak, Joanna Chen-Yeen; Seak, Chen-Ken
Abstract: Rationale: Abdominal pain in pregnancy represents a demanding diagnostic challenge in the emergency department (ED) due to the extensive list of differential diagnoses to be considered, coupled with the possibility of each disease having nonclassical, atypical signs and symptoms, resultant from the patient's pregnant state. Additionally, emergency physicians (EPs) face limitations on investigative imaging modalities because of the need to minimize fetal radiation exposure. EPs have to tackle this diagnostic challenge while performing a balancing act to maximize both maternal and fetal outcomes in a time-sensitive manner, becauser any delays in decision-making at the ED may threaten the safety of mother and child. Two common causes of abdominal pain in pregnancy presenting to the ED are acute appendicitis and ectopic pregnancy. The latter is almost always diagnosed by 10 weeks of gestation. Here, we report an extremely rare case of unilateral live spontaneous twin tubal ectopic pregnancy presenting past 12 weeks of gestation, diagnosed after magnetic resonance imaging (MRI) of the abdomen. Patient concerns: A 37-year-old gravida 2 para 1 at 12 weeks and 6 days of gestation presented to our ED with a 2-day history of right iliac fossa pain, not associated with vaginal bleeding, fever, diarrhea, and vomiting. On examination, she was tachycardic (pulse rate 124 beats/min) and hypertensive (blood pressure 142/88 mm Hg). There was marked tenderness and guarding at the lower abdomen. Diagnoses: Blood investigations were unremarkable, while abdominal ultrasonography found a live twin gestation with foetal heartbeats of 185 and 180 beats/min. MRI of the abdomen revealed an empty uterine cavity; 2 amniotic sacs and fetuses of diameter 10 cm, and a single placenta were noted in the right uterine adnexa. The patient was diagnosed with right live monochorionic diamniotic twin tubal pregnancy. Intervention: Our patient underwent emergency laparoscopic right salpingectomy. Outcomes: The operation was successful and her postoperative care remained uneventful up to discharge. Lessons: Ectopic pregnancy cannot be ruled out based on prior normal antenatal examinations and gestational age of >10 weeks. EPs should not hesitate to order MRI scans for further evaluation if ultrasonography and laboratory findings are equivocal.